Evidence of a Patient Centered Medical Home (PCMH) Improving the Health of Chronically Ill Patients in the Mississippi Delta - Wesley L. James; Karen C. Matthews; Peter A. Albrecht; Shelby Fox; Anna Church (Journal of Preventive Medicine And Care, 2017)
Using proprietary data of patient records from four medical clinics in the Mississippi Delta, this research utilizes a natural experiment design to explore if the patient centered medical home (PCMH) has a positive effect on chronic disease maintenance for low SES, majority African-American patients in a rural and medically underserved region. The patients are divided into two cohorts, those attending PCMH clinics (level 2) and those attending non-PCMH clinics. Each cohort is comprised of similar demographic, socioeconomic, and health (large proportion of diabetics) characteristics. HbA1c scores of the cohorts are compared at two time periods, baseline and six-month follow-up. PCMH patients report more uncontrolled diabetes at baseline but the trend reverses at follow-up, providing evidence that the PCMH model of primary care produces positive health outcomes for patients with diabetes in the sample area.
Keywords: Patient centered medical home